TRANSISI PEMUDA DALAM MASYARAKAT RISIKO: ANTARA ASPIRASI, HAMBATAN DAN KETIDAKPASTIAN - Oki Rahadianto Sutopo (Jurnal Universitas Paramadina, 2014)
This article explains about the aspirations, obstacles and uncertainties of  youth transition from school to work using youth transition and risk society  perspective. It is more difficult for young peopleto handle the transition in the  conditions of late modernity era. They have to deal withuncertainty and  risk without certain direction of their future. As one of the consequences in the  risk society, young people are more individualize to create their own  biographical trajectories.They have to make their own plans both related to  education and work. Individualization is becoming the new social structure,  where people seek biographical solutions to systematic contradictions  embedded in late modernity. However, youth transition from school to work  still has to deal with many layers of structural obstacles. As a solution, the  state role needs to be reinforced to protect young people from risk in the future.